2018
DOI: 10.3390/su10114282
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Thinking for Sustainability: A Review of 10 Strategies for Sustainable Mobility by Bus for Cities

Abstract: The sustainable mobility of the future comes about through sustainable ways of transport, such as walking, cycling, or collective transport. This includes the bus, the underground, and trains in big cities. This article reviews bus-related policies and initiatives worldwide. It also analyses ten cities looking at medium and long-term strategies for the urban bus service. The main ideas are: the forecasts for the use of the urban bus system indicate a significant increase in demand, therefore, there is a need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
(40 reference statements)
2
9
0
Order By: Relevance
“…Another suggestion to increase accessibility is to perform a viability study of offering the studied mobility services to medium and low-income areas, thus increasing the social impact of the initiatives. The proposed suggestions are in line with the strategies for sustainable mobility by bus reviewed by Fernández and Fernández [45], and also with the development of similar initiatives in Latin America.…”
Section: General Recommendations For Sustainable Mobility Initiativessupporting
confidence: 73%
“…Another suggestion to increase accessibility is to perform a viability study of offering the studied mobility services to medium and low-income areas, thus increasing the social impact of the initiatives. The proposed suggestions are in line with the strategies for sustainable mobility by bus reviewed by Fernández and Fernández [45], and also with the development of similar initiatives in Latin America.…”
Section: General Recommendations For Sustainable Mobility Initiativessupporting
confidence: 73%
“…The result showed that it is significant to allocate appropriate slack time to provide effective flexible line service. Dijosephl et al [37][38][39] developed an optimization algorithm to search for the maximal-profits optimal solution by considering the public transport network and passenger demand, as well as optimized the regional public transport system and financially sustainable operation.…”
Section: Coordination and Optimization Of Rail And Public Transportmentioning
confidence: 99%
“…Some of the studies that take into account fuel efficiency, traffic congestion, taxes on coal, and improvements in public transport conclude that a mix of strategic measures for public transport is the best option towards a sustainable environment [11]. Thus, the performance in infrastructure (either through BRT or exclusive bus lanes), electric vehicles or those running with new sources of energy such as natural gas and its positive impact on the drastic reduction of NO x [12], the application of technology for service improvement [13] and user information or route optimization, international research, and development or service improvement are some of the most important strategies, which are developed in the bibliography [13].…”
Section: Practical Experiencementioning
confidence: 99%